Interactive Multimedia Design Based on Cognitive Conflict on Dynamic Fluid Using Adobe Animate CC 2019 (Jurnal Pendidikan Fisika Indonesia, 2023)
In the 21st century Science and Technology (IPTEK) is experiencing very rapid development which requires students to have skills in that century. In addition, one of the objectives of learning physics in the 2013 curriculum is to have a good understanding of concepts and principles. However, in reality there are still obstacles in students' understanding of concepts that are still low, including dynamic fluid material. The solution given is to develop interactive multimedia based on cognitive conflict. This study aims to determine the characteristics of interactive multimedia design and determine its validity. This type of research is development research using the Plomp development model which is special to the preliminary research and prototyping stages to the expert review. Preliminary research data obtained from needs analysis through filling out a questionnaire by 3 physics teachers and the validity of the data obtained from 3 physics lecturers. The instruments in this study were teacher questionnaires, self-evaluation sheets and expert validity sheets. Data were analyzed descriptively. This research produces interactive multimedia with characteristics set according to 4 syntaxes of cognitive conflict-based learning models using the adobe animate cc 2019 application. Multimedia is designed to improve students' conceptual understanding of dynamic fluid materials and justify 4C skills. the results of self-evaluation show that multimedia is in the very good category.